Utilization of the heat from combustion of water for the heating process in water desalination - Permadi, Adi; Syamsuddin, Arief; Widyaningrum, Trianik; Satar, Ibdal; Suharto, Totok Eka; Pitoyo, Joko (International Journal of Advances in Applied Sciences, 2024)
The volume of municipal waste has become a national problem so far, so a solution is needed to reduce the waste problem. One solution to reduce the volume of municipal waste is to burn waste. However, the combustion needs to be designed to take advantage of the heat generated by combustion. In this study, the process of burning waste with various types of waste materials was carried out. The heat of burning waste is used to evaporate 1 liter of seawater and the seawater vapor is cooled to produce distilled water. The volume of distilled water and the precipitated salt were weighed. The results of the research from the variation of 6 types of waste materials obtained that the type of clothing waste material gave the fastest time, which was 43.75 minutes, the amount of distilled water was 931 ml, and salt deposited as much as 30 grams. The test results on distilled water showed that almost all parameters met the requirements of drinking water and obtained a salt content of 84%. Further processing by adjusting the hardness is needed to process distilled water into clean water and the addition of iodine can be considered to produce iodized salt.